Saturday

August 2, 2014

August 2, 2014

Posted by **Tim** on Thursday, March 13, 2008 at 11:51pm.

20x^2-12x+15x-9

= 20x^2+3x-9

= (4x+3)(5x-3)

- Algebra -
**Leo**, Thursday, March 13, 2008 at 11:53pmYes, looks good.

**Related Questions**

Algebra - Can someone tell me if I am right? Factor by group 20x^2-12x=15x-9 20x...

Algebra-Please check - 5 - sqrt of 20x + 4 >= -3 5- 20x + 4 >= -3 5-4 - ...

math,correction - Directions:Multiply Problem: ((x)/(3)+(3)/(4)) ((3x)/(4)-(3)/(...

algebra - Andrew factored the expression 20x^3-12x^2+8x as 4x(5x^2-12x^2+8x). ...

Algebra - Andrew factored the expression 20x^3-12x^2+8x as 4x (5x^2-12x^2+8x). ...

algebra 2 - find all the zeroes of: x^5-3x^4-24x^3-72x^2-25x+75=0 5x^5-20x^4-40x...

Algebra - Can someone help me with this please. Andrew factored the expression ...

math - 5(3+4x)-6>=129 I get 2 different answers on this one. 15+20x-6>=129...

algbrea - 3x-5(3x-7)= 2(x+9) + 45 3x-15x+35= 2x+18 +45 -12x + 35 = 2x+63 -12x -...

Algebra - Rewrite the middle term as the sum of two terms and then factor ...